Harold Frederic papers - Frederic, Harold, 1856-1898.
Correspondence, diaries, writings, notes for plays and stories, wills, agreements, accounts, clippings, printed matter, and other papers chiefly relating to Frederic's fiction writing. Includes notes for his principal novels, The Return of the O'Mahony (1892) and The Damnation of Theron Ware (1896).
Journalist, novelist, and playwright.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: American fiction; American literature; Frederic, Harold, -- 1856-1898.; Frederic, Harold, -- 1856-1898.; Journalists; Novelists; Playwrights